PUBLIC RELATION DINAS KEBUDAYAAN PARIWISATA PEMUDA DAN OLAHRAGA KABUPATEN PONOROGO DALAM MEMPROMOSIKAN PARIWISATA - Safira Rahmatika; Kayyis Fithri Ajhuri (Proceeding of Conference on Strengthening Islamic Studies in The Digital Era, 2023)
Public relations of the Youth Tourism and Sports Cultural Office of Ponorogo Regency plays a role in tourism promotion activities in Ponorogo Regency; therefore, it is necessary to know the media or promotional facilities, how to manage and obstacles and solutions provided to overcome these obstacles. The research method in this study uses a qualitative approach with descriptive analysis—data collection using interviews and documentation. Data analysis techniques using Miles and Huberman consist of three activities that co-occur: data reduction, data presentation, conclusion drawing, or verification. The results showed that the media used by the Culture, Youth Tourism and Sports Office of Ponorogo Regency in promoting tourism, namely (a) conventional media, radio, and television; (b) new media (internet); Instagram, YouTube, Facebook, and apps. (c) outdoor media: banners, billboards, leaflets. All media are used to manage tourism promotion activities such as advertising, personal selling, and public relations. The obstacles encountered by the Department of Culture, Youth Tourism and Sports of Ponorogo Regency in promoting tourism are two factors, namely internal and external. Internal obstacles include a lack of communication between official employees, which results in hampered promotional activities; the solution is to improve communication between employees so that promotional activities can be carried out according to deadlines. External obstacles are limited tourism promotion procurement costs from local governments, and the solution must be adequately managed so that the budget costs are distributed appropriately.